The Examination of the Wien’s Displacement Constant with Simulation and Simple Numerical Approaches - Aprilia, Riana; Alifaturrohmah, Marisa; Purnama, Gilang; Wahyuni, Siti (Universitas Negeri Semarang, 2022)
The purpose of this research was to examine the value of the Wien’s constant using PhET Simulation virtual laboratory and simple numerical approach. The independent and dependent variable is blackbody temperature (T) and maximum wavelength (λ_max). In the use of a virtual laboratory, research is carried out by shifting the black body temperature feature so the graph will display a spectral power density that varies to the wavelenght. Numerical approach was used in this research is Newton Raphson methods by Python program. Both of simulation and numerical approach yield the value of the maximum wavelength (λ_max) for a black body temperature variation. The black body temperatures and their appropriate maximum wavelength data then analyzed using linear regression. Final result show that value Wien’s constant using PhET is 2,93 × 10-3 mK with relative error obtained is 1,07 % while using Newton Raphson the Wien’s constant value obtained is 3,07 × 10-3 mK with relative error is 5,90 %. The two approachs carried out produce data that slightly different, but still in a very good accucracy range when compared with theory. So, PhET Simulation and Newton Raphson methods effective to examine the value of the Wien’s constant.